2018
DOI: 10.1615/plasmamed.2019028659
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Direct and Indirect Treatment with Cold Atmospheric Plasma on In Vitro and In Vivo Models of Wound Healing

Abstract: Cold-atmospheric plasma (CAP) produces a mixture of molecular, ionic, and raditherapeutic potential have been studied in disciplines such as dermatology, oncology, and dentistry. This study investigates both in vitro and in vivo-Plasma is generated in a helium jet using an alternating-current 50-Hz power supply at 32 kV and 90 mW. Results show that 1-min direct CAP treatment stimulates skin cell migration; however, cellular proliferation remains unchanged. Treatment > 3 min leads to cell death. Using the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Wound scratch assay was performed as described previously 14 , 39 . After confluent cultured cells grown in 24-well plates were obtained, the medium was replaced with 0.3% FBS containing DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…Wound scratch assay was performed as described previously 14 , 39 . After confluent cultured cells grown in 24-well plates were obtained, the medium was replaced with 0.3% FBS containing DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…In general, there are two ways to treat CAP to cells [21,22]. First, direct treatment can induce strong cell death by reaching the plasma species to the cells.…”
Section: Introductionmentioning
confidence: 99%
“…In other models, gas plasma-treated liquids were used as lavage. While one study found beneficial effects of direct gas plasma jet treatment and jet-treated liquids on wound healing [ 59 ], another report did not observe such results [ 60 ]. Both studies were done in Balb/c mice, with the former using helium and the latter an argon plasma jet.…”
Section: Gas Plasma Treatment Of Skin and Wounds In Animal And Veterinary Modelsmentioning
confidence: 99%